Determination of Recovery by Total Restitution or Compensation Using Multifrequency Vestibular Tests and Subjective Functional Scales in a Human Model of Vestibular Neuritis - Enrico Armato; Georges Dumas; Flavio Perottino; Matthieu Casteran; Philippe Perrin (Audiology Research)
Background: Vestibular Neuritis (VN) can induce unilateral acute vestibular syndrome (AVS). This study aimed to identify predictive factors of recovery from vestibular neuritis considering total restitution and/or compensation. Methods: In this longitudinal study, 40 patients were included. The initial assessment, performed within 36 to 72 h from the onset (T0), included medical history taking (general and specific), including screening for cardiovascular risk factors (CVRFs), and a battery of diagnostic vestibular tests, comprising the bithermal caloric test (BCT), video head impulse test (VHIT), and skull vibration-induced nystagmus (SVIN) test. All patients also completed a Dizziness Handicap Inventory (DHI). All assessments were repeated 90 ± 15 days later (T3). Subjective compensation criteria were based on the DHI total score, and objective compensation criteria were based on laboratory test results. Four groups of patients (A, B, C, D) were delineated by combining patients with normal vs. abnormal vestibular tests and patients with normal vs. abnormal DHI. Results: CVRFs (but not age or body mass index (BMI)) were associated with a poorer recovery of symptoms. The BCT (lateral semicircular canal paresis %), VHIT (lateral semicircular canal gain), and SVINT (nystagmus slow phase velocity) recovered to normal values in 20%, 20%, and 27% of patients, respectively, at T3. Conclusions: Vascular risk factors (hypercholesterolemia) are correlated with patients who do not recover their symptoms via either total restitution or compensation. There was no significant difference between high- and low-frequency vestibular tests in patients recovering from their symptoms. Some patients with objective recovery may continue to have persistent subjective symptoms.